Examination of The Mental Health Componet of Quality of Life of Haemodialysis Patients and Its Relationship to Perceived Expressed Emotion, Coping Self Efficacy, Optimism, Self Esteem, and Social Support - ÖZDEN Yalçýnkaya-Alkar; A. Nuray Karancý (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
ABSTRACT Objective: This study aimed to examine the mental health component of quality of life (MHC) of haemodialysis patients and its relationship with personal characteristics (two components of perceived expressed emotion (criticism/hostility and emotional over-involvement), optimism, self esteem, social support, and coping self efficacy related to symtom distress) and other resources within the Conservation of Resources(COR) Model (Hobfoll 1989). Method: Demographic variables and haemodialysis related information of patients, with the other resources classified as resources according to COR model, were also included in the study. One hundred and six haemodialysis patients voluntarily participated in the study. For the study, perceived expressed emotion, optimism, self-esteem, perceived social support and perceived coping self efficacy were taken as resources and were also included as measures. After examining the correlational matrix among the variables of, in order to examine variables related to MHC and test the main hypothesis of the study, multiple regression analysis was conducted. Results: The results of the analysis showed that age, income, house ownerhip, presence of additional diagnosis, self esteem, perceived criticism/hostility and coping self efficacy were significantly related to MHC. Directions of the relationship between age, presence of additional diagnosis, and criticism/hostility were negative with the outcome variables, whereas, directions of the relationship between income, house ownerhip, self-esteem and coping self-efficacy were positive with the outcome variable, MHC. Conclusion: Patients’ concerns about various aspects of demographic and illness related variables, perceived coping self-efficacy, self-esteem, and criticism-hostility were found to be predictive of their MHC. [JCBPR 2014; 3(1.000): 23-37]